Parents' Perception and Expectation of Islamic Private Preschool Education in Malaysia - Zaiton, Mustafa; Wan Abdul Hayyi, Wan Omar; Zanirah, Wahab; Suffian Hadi, Ayub; Sharipah Nur Mursalina, Syed Azmy; Nurazan, Mohmad Rouyan; Hishamuddin, Salim; Nor Hafizah, Abdullah (2017)
Islamic private preschools have been gaining popularity in Malaysia over the past years. The increasing number of Islamic private preschools indicate that the demand from parents is high. Moreover, some parents even look for branded Islamic preschool for their children. This study was conducted to investigate parents’ perception of the branded Islamic private preschool and what do they expect from their children’s learning experiences in the chosen preschools. The participants of this study consist of six parents from three selected Islamic preschools. In depth semi structured interviews had been employed by the researchers to collect the data. Based on the findings, parents perceive that Islamic preschools have a significant role as an early educational centre to inculcate Islamic teachings for their children. The study also found that parents expect the well-being of their children spiritually, physically, mentally and emotionally through their learning experiences in the chosen preschools.